Comparison of Growth Velocity Among School Age Children With Different Body Mass Index From Childhood Into Early Adolescence in Hualien County, Taiwan: A Retrospective Cohort Study - Hsiao, Yu-Chao; Wang, Jen-Hung; Chu, Chia-Hsiang; Chang, Yu-Hsun; Chen, Jui-Shia; Jan, Rong-Hwa; Yang, Shang-Hsien; Chen, Ming-Chun; Chou, Wei-Chih; Chu, Shao-Yin; Lai, Pei-Chun; Cheng, Ching-Feng; et al. (Frontiers in Pediatrics, 2021)
Objective: This study aimed to investigate the contribution of high body mass index (BMI) to growth velocity among elementary students who remained in the same BMI categories for a 6-year period. Methods: This retrospective cohort study included children who enrolled in the school year 2009 and remained in the same BMI categories during their 1st, 4th, and 7th grades (6-7, 9-10, 12-13 years of age). Annual linear growth velocity and weight gain were calculated and compared between sexes, BMI groups, and different times. Risk analysis and repeated measures analysis of variance were performed to identify the impact of BMI on growth velocity. Results: Of the 1,637 subjects, 53.0% were male, and 2.5% and 10.9% belonged to BMI groups of overweight and obese, respectively. In students between 6 and 13 years of age, obesity was associated with higher annual weight gain and height gain. Risk analysis showed that obese subjects had higher linear growth velocity than normal BMI groups of both sexes between 6 and 9 years of age. Unexpectedly, overweight and obese girls between 9 and 13 years of age had less linear growth velocity than underweight girls at the same interval. Repeated measures analysis of variance in both sexes showed a significant statistical association between BMI and different times of growth. However, the effect was less in girls between 9 and 13 years of age. Conclusion: Puberty may dominate over BMI as the main contributor to high growth velocity in girls with underweight BMI emerging into pubertal age.